Reframing Joseph Cardinal Bernardin's Consistent Ethic of Life in the Light of the Crisis or Our Common Home and Pope Francis' Integral Ecology - Aseneta, Anatoly Angelo (Archīum Ateneo, 2019)
As raised by Pope Francis in Laudato Si’ and as evidenced by the various ecological problems we face, the crisis of our common home harms not only non- human but also human life. Consequently, it is becoming more evident that to consistently defend human life inevitably means caring for our common home. Joseph Cardinal Bernardin’s moral vision of a consistent ethic of life (CEL), reframed in the light of the crisis of our common home and Francis’ call for an integral ecology, can provide a moral framework that inseparably links the protection of human life with caring for our common home. While Bernardin did not include ecological concerns under the CEL, it is argued that his moral vision must pay attention to the modern ecological crisis because of its moral dimensions, the “slow violence” against life behind it, and its relationship to technological questions. The similarities between Bernardin and Francis as well as their respective visions allow integral ecology to expand the CEL and provide it with a stronger language of interconnections. In turn, a reframed CEL can provide a moral vision for Francis’ appeal for consistency in living out integral ecology and that enables us to see that caring for our common home is ultimately a “pro-life” issue. This reframing process begins with a theological and historical analysis of both the CEL and integral ecology. The two visions then enter into a dialogue with a primary focus on the consistent ethic of life as it reframed. Finally, an attempt is also made to identify how to concretely live this reframed ethic, particularly in the Filipino milieu. The hope is for us to expand our moral universe and see that to consistently protect human life we must also care for our common home.